The New Normal Leadership: How Technology Alter Communication Style in Contemporary Organization - Taufan Teguh Akbari; Rizky Ridho Pratomo (Ikatan Sarjana Komunikasi Indonesia, 2021)
The Covid-19 pandemic has hit many sectors in the world. To mitigate the plague, many countries have formulated a social distancing policy. The pandemic compels us to foster the use of technology to carry out daily activities. A very few articles explain how technology alters the way leaders communicate. Therefore, the Â objective of this research is to examine whether technology has an impact on leader communication patterns using Adaptive Leadership and Technological Determinism Theory. This research uses qualitative approach with literature review and interview as a means to collect and analyze data. Based on the current trend, there are some changes in leader communication patterns. Also, the author found that there is a gap in the adoption of technology between leaders and members of the organization. While leaders are prepared to change mindset and embraceÂ digital Â practices, members are not well-prepared. They struggle to adjust to the new work environment and feel overworked and exhausted. To embrace the digital working environment, leaders need to solve the gap. We argue that the gap between the leaders and members can be addressed by enhancing or improving the way leaders and members interact. This is because to become a leader, one should engage in communication. We propose some principles about new ways of communication during the New Normal.